The Two Books of God - Frye, Roland Mushat (Theology today, 1982)
“We have available to us not just one book of God, but two: the book of God's word in Scripture, which concerns the ultimate nature and destiny of humanity, and the book of God's works in nature, which deals with the conditions of the created order…. The entire flowering of modern culture, and derivatively of modern technology, grew out of this essentially religious conception of the two books of God.”